Can children predict psychological recovery after injury?. Issue 12 (26th September 2019) - Alisic, Eva; Mangelsdorf, Shaminka N; Schilpzand, Elizabeth J; Barrett, Anna; Landolt, Markus A; Mehl, Matthias R
Abstract : While children's voice is core to paediatric care, their own assessment of future psychological needs is underexplored. We conducted a prospective observational study among children hospitalised for injury in Melbourne, Australia. Their expectations of psychological recovery at baseline (in hospital) were significant and substantial predictors of their quality of life and post-traumatic stress 6 weeks later, suggesting potential diagnostic value.